Analysis of Competitive Strategies in Micro Credit Marketing at BANK BTPN Tangerang Region - Ardiyanti, Anita (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The aim of this research is to identify the strengths, weaknesses, threats and opportunities for marketing micro credit at Bank BTPN. Identifying the applied micro credit marketing strategy. Identifying strategies to win the microcredit competition. The research method used is the mix method combining qualitative and quantitative. The population is Regional Business Sales Support Manager, Regional Credit Manager, Business Area Leader, Branch Manager, all of whom are in the Tangerang region. The conclusion in the analysis of the micro credit strategy set at Bank BTPN Tangerang Region is that the micro credit marketing development strategy is carried out by analyzing the strengths, weaknesses, opportunities and threats, using a SWOT analysis. Identification of threats, strengths, weaknesses and opportunities regarding microcredit marketing at Bank BTPN Tangerang Region. Being able to develop the business according to the SWOT analysis, Bank BTPN as a people's business partner, has four strategies that are weighted according to the highest score. SO (strength-opportunity) strategy (1). Expanding the regional market network by utilizing branch networks in the regions (2). Developing products and services based on digital technology, for new customers and prospective customers, Btpn launched the Genius digital application and btpn WOW